2011
DOI: 10.1002/eji.201041075
|View full text |Cite
|
Sign up to set email alerts
|

Batf3 transcription factor‐dependent DC subsets in murine CMV infection: Differential impact on T‐cell priming and memory inflation

Abstract: Priming of CD81 T cells specific for viruses that interfere with the MHC class I presentation pathway is a challenge for the immune system and is believed to rely on cross-presentation. Cytomegalovirus (CMV) infection induces vigorous CD8 1 T-cell responses despite its potent immune evasion strategies. Furthermore, CD8 1 T cells specific for a subset of viral epitopes accumulate and are maintained at high levels exhibiting an activated phenotype -referred to as ''inflationary T cells''. Taking advantage Batf3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
87
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(98 citation statements)
references
References 28 publications
9
87
1
Order By: Relevance
“…Our finding corroborates and extends the results of two other recently published studies. Torti et al (55) showed that priming of MCMV-specific CD8 + T cells was severely impaired in Batf3 knockout mice, which are compromised in the development of CD8a + and CD103 + DC subsets. This pointed to a prominent role for cross-presentation, but left open whether the residual T cell priming observed resulted from direct priming or from other remaining APCs in these mice that are capable of cross-presentation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our finding corroborates and extends the results of two other recently published studies. Torti et al (55) showed that priming of MCMV-specific CD8 + T cells was severely impaired in Batf3 knockout mice, which are compromised in the development of CD8a + and CD103 + DC subsets. This pointed to a prominent role for cross-presentation, but left open whether the residual T cell priming observed resulted from direct priming or from other remaining APCs in these mice that are capable of cross-presentation.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study suggested that differentiation of T cells primed early in infection, as well as de novo priming of naive T cells during chronic infection, contribute to the expansion and maintenance of certain effector memory T cells at high levels (79). Recent results indicated moreover that cells of nonhematopoietic origin are involved in this process (55,80,81). We hypothesized, therefore, that stochastic expression of the major immediate early promoter-driven reporter genes by latently infected host cells may also give rise to T cells recognizing the signal peptide-encoded epitopes.…”
Section: Predominance Of Cd8 + T Cells Generated Via Cross-presentatimentioning
confidence: 99%
See 2 more Smart Citations
“…5B). Although we cannot entirely exclude a residual cross-presentation capacity of other DC (34) or macrophage subsets (35) in the Batf3 null mice, this contribution to Ag presentation has been reported to be inefficient in this setting (17,36). When taken together with the OT-1 CD8 + T cell priming observed by our adoptive DC transfer system in the K bm1 mouse (Fig.…”
Section: Discussionmentioning
confidence: 83%